Common Risk Factors related Toxoplasmosis Infection during pregnancy - Ameen , Wafaa Ahmed; Humade, Saadya Hadi (International Journal of Psychosocial Rehabilitation, 2026)
Toxoplasmosis a foremost cause of death recognized to foodborne illness. More than 40 million men, women, and children in the U.S. women newly infected with Toxoplasma during or shortly before pregnancy should be alert that toxoplasmosis may have severe consequences. Objectives: to assess risk factors of toxoplasmosis among the pregnant women. Methodology: A descriptive analytic study was conducted on (100) of pregnant women. Who attending at primary health care centers in AL - Hilla city they have previous or positive test for toxoplasmosis? Data collected for the period of (13thFebruary - 30th July 2019) and; including characteristics (socio, reproductive); and Risk factors. Results: showed that high significant association between demographical variables (age with dietary and hygiene) and significant association between education with dietary and between residence and hygiene) high significant association between reproductive variables(gravid, para with dietary and hygiene) and high significant association between abortion, stillbirth ,visiting health centers with dietary factors . Conclusion: Pregnant women must be changing some dietary behaviors and also following personal hygiene when contact with meat and vegetables.